A thematic analysis of the Excel Pre-Collegiate Program as an avenue of successful postsecondary enrollment for Latina/o students - Armendariz, Cynthia Núñez, author; Aragon, Antonette, advisor; Anderson, Sharon, committee member; Jennings, Louise, committee member; Scott, Malcolm, committee member (Colorado State University. Libraries, 2017)
College access and college enrollment rates are significantly lower for students of color, students from lower socioeconomic backgrounds, and first-generation students (Reese, 2008). High schools, universities, and state and federal agencies have all recognized that the gap in college enrollment between students of color and their white counterparts is a major issue (Loza, 2003). High schools have implemented college prep classes and dual enrollment programs, universities have built bridge and pre-college programs, and the federal government has implemented legislation and provided funding geared at closing the enrollment gap between students of color and white students (Reese, 2008). Even with the various forms of interventions, the issue of low post-secondary enrollment specific to students of color continues. This study examines the experiences of Latina/o students who participated in the Excel Pre-Collegiate Program, a pre-college program offered through Metropolitan State University of Denver. In addition, the study explored how the participants' culture and background influenced their college-going and general educational experience. The study found that pre-college programs are an important and needed opportunity for students to gain the skills and knowledge to successfully navigate the college application process and enroll in college. Pre-college programs address many of the barriers and challenges that deter Latina/o students and students of color in general from attending higher education institutions.
Keywords: Latina/os; pre-collegiate; pre-college; college enrollment